HABITAT IKAN PELANGI ARFAK (Melanotaenia arfakensis ALLEN) BERDASARKAN TAHAP PERKEMBANGAN DI SUNGAI NIMBAI DAN SUNGAI AIMASI, MANOKWARI - Emmanuel Manangkalangi; M. F. Rahardjo; Djadja S. Sjafei (Jurnal Natural, 2009)
The habitat ontogeny of arfak rainbowfish (Melanotaenia arfakensis Allen) in Nimbai and Aimasi streams, Prafi river system were studied from June to December 2007. Sampling was carried out monthly in four different habitat types using hand net. Slow littoral and medium littoral are two habitat types which characterized by slowly water velocity, availability of submerged vegetation and warmer temperature, however the run and pool areas have higher water velocity and dissolve oxygen. The former habitats are essential for all developed stages, i.e. feeding, spawning and nursing of this species. On the other hand, the later habitat types particularly were only for young and adult fish, due to their swimming abilities as well as maximize of oxygen uptake. In order to maintain the population of this species, conservation is needed to all of their natural habitats for continuing their life cycles.